An update on the diagnosis and treatment of adrenoleukodystrophy. Issue 1 (14th February 2023) - Gujral, Jasmine; Sethuram, Swathi
Abstract : Purpose of review: The present review summarizes recent advances in the diagnosis and management of patients with X-linked adrenoleukodystrophy (ALD). Recent findings: Although ALD screening has been on the list of Recommended Uniform Screening Panel since 2016, only 30 states in the United States are currently testing their newborns for this disease. Hematopoietic stem cell transplant (HSCT) remains the only successful treatment option available for early cerebral ALD but does not reverse neurological changes or affect the course of adrenal insufficiency. There remains a significant knowledge gap in our understanding and treatment of this disease. Novel therapies such as gene therapy and gene editing have shown promising results in animal models and are exciting potential treatment options for the future. Recently, the American Academy of Neurologists released their consensus guidelines on the diagnosis, surveillance, and management of ALD. Summary: Early diagnosis and HSCT are key to improving the morbidity and mortality associated with ALD. The implementation of universal newborn screening for ALD and rigorous investigations of novel diagnostic and therapeutic agents is the need of the hour.